PENDIDIKAN KECAKAPAN HIDUP (LIFE SKILLS) MELALUI CHILD FRIENDLY TEACHING MODEL (CFTM) SEBAGAI DASAR MEMBANGUN KARAKTER SISWA - Muhdi IKIP PGRI Semarang; Senowarsito IKIP PGRI Semarang; Listyaning S. (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2012)
AbstractLife-skills education is an educational model that builds hard skills and soft skills in an integrated way. Strengthening students' soft skills will strengthen the hard skills and vice versa. Characterized person is one who is able to keep upright the soft skills and hard skills as an attitude and a behavior in society. Child Friendly Teaching Model (CFTM) is a model that will build life skills to deal with four pillars of the Child Rights Convention, namely non-discrimination, best interests of the child; the rights to life and development; the right be heard and express its views, by strengthening of 3Ps (Provision , Protection, and Participation). This model endorses children to be met early in the child's rights to live, grow, develop and participate optimally in accordance with human dignity. Life skills education can be done through: 1) habituating in the school and classroom environment, 2) manipulating the content of the materials, 3) correcting and reinforcing behavior, and 4) manipulating the learning activities. Learning activities that have a nurturing effect on building character are collective, interactive, cooperative, and reflective learning with respect to children's rights through the strengthening of 3Ps.Key Words: Life Skills, Hard Skills, Soft Skills, Character Education, CFTMAbstrakLife-skills education adalah model pendidikan yang membangun hard skills dan soft skills secara terintegrasi. Penguatan soft skill siswa akan menguatkan hard skillsnya demikian juga sebaliknya. Orang yang berkarakter adalah orang yang mampu menyeimbangkan soft skill dan hard skills dalam bersikap dan berperilaku dalam masyarakatnya. Child Friendly Teaching Model (CFTM) adalah sebuah model pendidikan yang akan membangun kecakapan hidup siswa dengan meperhatikan empat pilar. Konnvensi Hak Anak yaitu non-diskriminasi; kepentingan terbaik bagi anak ; hak untuk hidup dan berkembang; hak untuk mengemukakan pendapat, melalui penguatan 3P (Provision, Protection, dan Participation). Melalui model ini, anak sejak dini diharapkan akan terpenuhi hak hak anak agar dapat hidup, tumbuh, berkembang dan berpartisipasi secara optimal sesuai dengan harkat dan martabat kemanusiaan. Pendidikan kecakapan hidup dapat dilakukan melalui: 1) pembiasaan di lingkungan sekolah dan kelas; 2) memanipulasi isi materi; 3) penguatan dan koreksi perilaku; dan 4) memanipulasi aktifitas pembelajaran. Aktivitas pembelajaran yang mempunyai nurturing effect terhadap pembentukan karakter adalah aktivitas pembelajaran yang bersifat kolektif, interaktif, kooperatif, dan reflektif dengan memperhatikan hak-hak anak melalui penguatan 3P.Kata Kunci: Life Skills, Hard Skills, Soft Skills, Pendidikan Karakter, CFTM